MENGUNJUNGI TEMPAT SUCI; RAGAM MOTIVASI WISATA RELIGIOUS - Ah. Fawaid, Ah. Fawaid (STAIN PAMEKASAN, 2012)
Â Ah. Fawaid (Penulis, dosen STAIN Pamekasan, Jl. Pahlawan Km. 04 Pamekasan, Kontak, fawaid.sjadzili@gmail.com) Â Â Abstract The journey to the sacred place is a fairly old tradition. In the history of ancient civilization, the sacred place became a magnet for religious believers to do the pilgrimage and magical rituals. The sacred place has become a tourist object from generation to generation. To visit the sacred place is not always identical with rural communities, communities that often are identified as followers of khurafat. Visiting the sacred place is also a city-educated public interest. Like the form of tourism in general, visiting the sacred place may be just pure entertainment, education, or indeed release a spiritual thirst for community. Kata-kata kunci tourism, wisata religius, migrasi, travel